PENGEMBANGAN MEDIA E-BOOK IPAS MATERI SISTEM PERNAPASAN MANUSIA UNTUK MENIINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Ananti, Nuralia; Albertus Hartana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of science and technology requires the utilization of innovative learning media in the teaching and learning process at the elementary school level. This study aims to develop a high-quality and effective IPAS e-book media on the human respiratory system to improve the learning outcomes of fifth-grade elementary school students. The research method employed was Research and Development (R&D) using the ADDIE model. The e-book development followed five ADDIE stages: (1) Analyze, conducting interviews with teachers and students (2) Design, designing the e-book framework (3) Development, developing the product and conducting validation tests. The e-book was validated by four validators, consisting of a subject matter expert, a science education expert, and two fifth-grade elementary school teachers (4) Implement, conducting a product trial in grade V at SD Karitas Nandan and (5) Evaluate, evaluating the validation results as well as the pre-test and post-test outcomes. The product validation results obtained a score of 3.75, categorized as very good and feasible for implementation after revision. The pre-test and post-test results showed an increase from 35% to 67.5%, indicating an improvement of 32.5%. Therefore, the IPAS e-book media on the human respiratory system can help improve the learning outcomes of fifth-grade elementary school students and is suitable for use in learning activities.